An approach to work design: in-depth audit to determine the modifiers of musculoskeletal disorder symptom among vehicle maintenance personnel - Shukriah Abdullah,; Baba Md Deros,; Nor Kamaliana Khamis,; Jaharah A. Ghani,; Sholehah Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Vehicle maintenance personnel maintain, install, dismantle and repair as well as use hand tools in the nature of their job. A study in this domain has its complexities as there are not many research regarding the vehicle maintenance industry. The purpose of this paper was to identify the factors and their relationships towards the development of musculoskeletal disorder (MSDs) among vehicle maintenance workers. Using a self-reported questionnaire, 150 participants from workshops in Malaysia were involved in this study. They consisted of 50 workers maintain cars, 50 workers maintain four-wheel vehicles, and 50 workers maintain buses. The exclusion criterion was the participant has not been involved in accidents that caused injuries such as bone fractures as well as tears in joints, ligaments, and muscles for the past 12 months. Statistical analysis was performed to assess the impact of risk factors on MSD prevalence. Through regression analysis, it was revealed that psychosocial, temperature, and posture factors were associated with symptoms of MSD prevalence with p < 0.05. Age, working hours, type of vehicle repair and body mass index also showed a significant relationship with MSD prevalence. Concerning the sources of risk, related factors, mechanism of injury, and potential intervention strategies to reduce the risk, this paper will focus on the causes, nature, severity, and degree of work-relatedness of MSDs. This identification of risk factors among vehicle maintenance workers can be used to better characterise the magnitude of the problem and formulate targeted prevention strategies with improved surveillance and more accurate data collection.